Falsafat al-Qiṣṣat fī al-Qur'ān wa Dauruhā fī Binā'i al-Shakhṣiyyat min Khilāli Qiṣṣati Mūsā wa al-Khidr: [The Philosophy of Quranic Narrative and Its Significance for Character-Building Based on the Story of Moses and Khidr] - Mohammed Adam Mohammed Abdulali; Machasin Machasin; Abdul Mustaqim (UIN Sunan Kalijaga Yogyakarta, 2021)
This paper seeks to understand the significance of the story of Moses and Khidr PBUH to develop character-building, whose actions seemed to contradict the teachings of Sharia. As one of the most prominent accounts in Islamic tradition, the long journey of Moses for receiving knowledge meets an end by encountering Khidr, an acquaintance with unique personalities who later becomes his mentor. As literary research on the Quranic tales, the discussion adopts inductive-analytical methods to describe the semantic and rhetorical aspects contained from Moses and Khidr’s relationship. Those aspects are further analyzed to instill noble virtues thoroughly. By contemplating Khidr’s confrontation toward Moses, the acts contain good reasons despite their figurative meanings may be misinterpreted as a call for evil deeds against weaklings. The results commemorate the significance of contemplation and patience and reemphasize that none shall rushing adjudicate the occurring issues because there may be wisdom in something incomprehensible. Learning from the story of Moses and Khidr, this article argues that decision-makers should incorporate with the people, and whoever takes distance from its people is incapable of solving problems.